Behaviour of pre-parturient sows housed in intensive outdoor or indoor systems - Hötzel, Maria José; Filho, Luiz Carlos Pinheiro Machado; Costa, Osmar Antônio Dalla (Pesquisa Agropecuaria Brasileira, 2005)
This work compared the behaviour of pre-parturient sows housed in intensive confined and outdoor systems, during the morning and afternoon prior to delivery. Eight sows were kept individually in farrowing crates or in paddocks with access to fresh pasture from 8 to 10 days before expected parturition. All outdoor sows built a nest within 24 hours before farrowing. On the morning and afternoon before farrowing they spent 6.5% of the time collecting grass and 7.5% of the time organizing the nest. Outdoor sows were observed more often than confined sows rooting (4.60% vs. 0.25%), feeding (10.2% vs. 3.0%), standing (51% vs. 13%) and walking (8% vs. 0%). Indoor sows redirected the nesting behaviour to other behaviours like attempts to dig the ground, nosing, biting and rooting parts of the crate, feeder or drinker, during 4.7% of the time. They also spent more time than outdoor sows inactive (85% vs. 60%), lying (72% vs. 41%), drinking (2.1% vs. 0.5%) and vacuum chewing (3.7% vs. 0.1%). The pre-parturient behaviour of sows was considerably affected by the husbandry system. The outdoor system appears to be more appropriate for the sows' welfare than the conventional confinement.